The smart phone study: assessing the reliability and accuracy of neonatal jaundice measurement using smart phone application - Swarna, Srujana; Pasupathy, Sekar; Chinnasami, Balaji; D., Nirmala Manasa; Ramraj, Balaji (International Journal of Contemporary Pediatrics, 2018)
Background: Current gold standard for bilirubin estimation in newborns is invasive while transcutaneous bilirubinometer which is a noninvasive option is costly. Smart phone applications can be used as an alternative to measure bilirubin. We did the study to evaluate “Biliscan” medical application for screening of neonatal jaundice. Methods: During the first seven days, neonates with suspected jaundice were taken blood samples for serum bilirubin. Within two hours photographs were taken using Biliscan app by placing a colour calibration card over the chest. Bilirubin estimate obtained after colour balancing, feature extraction and machine learning regression were compared with blood values. Results: There is a good correlation (0.6) between Biliscan bilirubin estimation and serum bilirubin levels (p <0.0001) in the present study on 35 neonates. Biliscan thorax values correlated better than abdomen values (0.6 versus 0.551) with serum values. Hence chest is the preferred area for Biliscan measurement. Conclusions: Biliscan app appears to be a good cheap option to screen for jaundice in newborns noninvasively.